2015
DOI: 10.18632/oncotarget.3469
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA ITCH has inhibitory effect on ESCC by suppressing the Wnt/β-catenin pathway

Abstract: Circular RNAs with exonic sequences represent a special form of non-coding RNAs, discovered by analyzing a handful of transcribed genes. It has been observed that circular RNAs function as microRNA sponges. In the present study, we investigated whether the expression of circular RNAs is altered during the development of esophageal squamous cell carcinoma (ESCC). Using a TaqMan-based reverse transcriptase polymerase chain reaction assay, the relationship between cir-ITCH and ESCC was analyzed in a total of 684 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
572
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 617 publications
(587 citation statements)
references
References 49 publications
(53 reference statements)
14
572
0
1
Order By: Relevance
“…It was shown that cir-ITCH expression is typically downregulated in esophageal squamous cell carcinoma. 44 This circular RNA could increase the level of ITCH by acting as miRNA sponge. In another study, cir-ITCH was shown to play an inhibitory role in colorectal cancer by regulating the Wnt/b-catenin pathway.…”
Section: Cardiovascular Diseasementioning
confidence: 99%
“…It was shown that cir-ITCH expression is typically downregulated in esophageal squamous cell carcinoma. 44 This circular RNA could increase the level of ITCH by acting as miRNA sponge. In another study, cir-ITCH was shown to play an inhibitory role in colorectal cancer by regulating the Wnt/b-catenin pathway.…”
Section: Cardiovascular Diseasementioning
confidence: 99%
“…For example, the circRNA circ-ITCH contains binding sites for miR-7, miR-17, and miR-214 and represses the activity of these microRNAs. 1 To serve as a sponge, however, a circular RNA has to contain many microRNA binding sites and be expressed at sufficiently high levels in cytoplasm. The majority of circRNAs may not be in this category and their functions remain uncertain.…”
mentioning
confidence: 99%
“…Recent studies have revealed that abnormal circRNAs are associated with several human diseases, such as atherosclerotic vascular disease, cancer and autoimmune disease 22, 23, 24, 25, 26. Many dysregulated expression circRNAs are demonstrated to associate with RA 16, 17.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that miRNAs and lncRNA are involved in the pathogenesis of RA and can be used as biomarkers for the diagnosis of RA 8, 9, 10, 11. Increasing evidence reveals that circRNAs are used widely in various physiological and pathological conditions, such as atherosclerotic vascular diseases, neurological disorders, prion infection and cancer 12, 13, 14, 15. However, little is known about the roles of circRNAs in human RA.…”
Section: Introductionmentioning
confidence: 99%